Правила для авторів - Problems of Cryobiology and Cryomedicine, Editorial Board (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4): 253-254